Kualitas Pelayanan Publik di UPT Puskesmas Perangai - Runni Runni; Titi Darmi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
The purpose of this study is how the quality of public services at the UPT Puskesmas Warai. In this study, the researcher used a qualitative descriptive research method, namely the method of observation, interview, and documentation. The results showed that public services at the Warai Lahat Health Center UPT were in accordance with five dimensions, namely Tangible, Reality, Responsiveness, Assurance, and Empathy. that are adequate and meet the standards for the needs of the people who visit the UPT Puskesmas Warai Lahat and can be categorized as having fulfilled the five dimensions of Public Service. The conclusion of the study is that the quality of public services at the UPT Puskesmas Warai, Lahat Regency, for service quality is good according to the SOP, the Puskesmas environment is clean, neat and comfortable, the availability of hand washing places, seats and trash boxes. Keywords: Publik Service, UPT Puskesmas